2021
DOI: 10.15244/pjoes/129697
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cellulase Production from <i>Bacillus albus</i> (MN755587) and Its Involvement in Bioethanol Production

Abstract: Cellulose, hemicelluloses, and lignin are the main consistent of the lignocellulosic biomass. Cellulose bonds strongly with hemicellulose and lignin [1]. Cellulose (C 6 H 10 O 5 ) appears as a closely packed dense structure when crystallized. It comprises thousands of glucose subunits linked by a linear β-1,4-glycosidic linkage. The efficient usage of the cellulosic wastes products for the economical production of cellulose through the development of sustainable systems has recently gained interest [2]. Worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Consistent with the obtained results, Abada et al . [ 11 ] reported that the maximum cellulase activity (19 IU/ml) produced by bacterial strain B. albus was attained at an inoculum size of 3% (v/v). On the other hand, cellulase enzyme was more active at an inoculum size of bacterial strain B. licheniformis 1-1v with a concentration of 1% [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the obtained results, Abada et al . [ 11 ] reported that the maximum cellulase activity (19 IU/ml) produced by bacterial strain B. albus was attained at an inoculum size of 3% (v/v). On the other hand, cellulase enzyme was more active at an inoculum size of bacterial strain B. licheniformis 1-1v with a concentration of 1% [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cellulase enzymes from thermotolerant bacteria are essential in the production of bioethanol and other biofuels, as they convert cellulose into fermentable sugars during the biomass conversion process. The enzymes' thermotolerance is particularly useful in these procedures since it accelerates and improves cellulose degradation, leading to greater biofuel yields [ 11 ]. Thermostable cellulases have uses in agricultural sectors and the feed industry.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, cellulose or lignocellulose can be used for the biological production of cellulase using bacterial or fungal organisms [8]. So, using bacterial or fungal enzymes, cellulose or lignocellulose can be used to produce cellulase through a biological process [9]. It is synthesized by plants and can provide energy and renewable chemicals in bio manufacturing to create a sustainable bio-economy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most organic solvents and water are insoluble in it [11]. On the other hand, these traditional procedures could result in hazardous contamination of the environment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulase production has been extensively studied in the bacterial genus Bacillus . Numerous aerobic bacterial strains, including Bacillus megaterium [12], Bacillus albus [13], Bacillus subtilis [14], Bacillus cereus [15], Bacillus circulans [16], Bacillus pumilus [17], Cellulomonas uda [18], Cellulomonas flavigena [19], Cellulomonas fimi [20], and some anaerobic bacteria, including Clostridium thermocellum [21] and Fibrobacter succinogenes [22] reported to produce cellulase enzyme.…”
Section: Introductionmentioning
confidence: 99%